Online Marriage Registration Service Policy Through Simkah Web for Prospective Bride and Groom in The Office of Religious Affairs, Banda Sakti District, Lhokseumawe City - Muksalmina Muksalmina; Muntasir Muntasir; Rasyidin Rasyidin; Mulyadi Mulyadi (Malikussaleh Social and Political Reviews, 2021)
The purpose of this study is to to the Circular Number of the Director General of Islamic Guidance: P-006/DJ.III/Hk.00.7/06/2020 dated June 10, 2020 regarding online marriage registration services through the Website: Simkah.Kemenag.go.id. The location of this research is KUA, Banda Sakti District, Lhokseumawe City. This study aims to determine the policy of online marriage registration services through Simkah Web for prospective brides at the Office of Religious Affairs, Banda Sakti District, Lhokseumawe City. The theoretical perspective used is policy theory according to Edward III (Resources, Disposition, Bureaucratic Structure and Communication). The research method used is qualitative research with the technique of determining informants using purposive and snowball techniques. The data were obtained by using the methods of observation, interviews, and documents. The results showed that: 1) The availability of human resources at the Office of Religious Affairs in Banda Sakti Sub-district was still very lacking who became SIMKAH WEB Operators so that it was difficult to deal with people who registered for marriage which in almost a month reached an average of 45 pairs. 2) Lack of socialization of the Simkah Web Application by KUA Banda Sakti District to the community so that there are still many people who do manual marriage registration. 3) There is no clear Standard Operating Procedure (SOP) for online marriage registration.